Study on Morphological Characteristics of Leaves, Shoots and Fruits of Selected Brinjal Varieties/Lines Influencing Brinjal Shoot and Fruit Borer Infestation - S. M. R. Amin; M. Z. Alam; M. M. Rahman; M. M. Hossain; I. H. Mian (International Journal of Economic Plants)
Morphological characteristics of leaves, shoots and fruits of 5 brinjal varieties/lines viz., BL 099, BARI Brinjal-6, BL 117, BL 072 , BARI Brinjal-1 and wild Solanum torvum were studied at the experimental farm and laboratories of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur during the period from September 2004 to April 2005 in a randomized block design with three replications. Higher number of leaves (195.50 plant-1) inviteshigher shoot and fruit infestation which was found positively correlated (r2= 0.55). Higher leaf area (63.53cm2/leaf and leaf trichom (256.7/25mm2) had lower shoot and fruit infestation which was found negatively correlated (R2 =0.65). Among the morphological characteristics of shoots viz., number of shoot, daimeter and length of top inter node have a positive correlation (R2=0.69, 0.85, 0.44) and number of prickles and trichome on shoot have a negative correlation (R2 =0.22,0.70) with BSFB infestation on brinjal shoot. The morphological characters of fruits like fruit per plant, calyx length, fruit length, diameter, shape and color have significant effect on BSFB infestation. Diameter of fruit, weight of fruit has a positive correlation (R2=0.14, 0.10) and length of fruit (R2=0.36) and calyx (R2=0.79) have a negative effect on BSFB attacking brinjal fruit.